2020
DOI: 10.3390/w12092570
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Attributes for Identifying Homogeneous Flood Regions for Regional Flood Frequency Analysis in Canada

Abstract: The identification of homogeneous flood regions is essential for regional flood frequency analysis. Despite the type of regionalization framework considered (e.g., region of influence or hierarchical clustering), selecting flood-related attributes to reflect flood generating mechanisms is required to discriminate flood regimes among catchments. To understand how different attributes perform across Canada for identifying homogeneous regions, this study examines five distinctive attributes (i.e., geographical pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This versatility of the G2P design storm makes it particularly useful in the context of practical urban hydrology applications at a regional scale. In fact, many studies estimating the impacts of global climate change present their results on a regional basis, referring results to expected spatial and temporal variations of given climatic or hydrological variables [52][53][54][55][56][57]. Such variables include precipitation, streamflow and temperature, among others.…”
Section: Discussionmentioning
confidence: 99%
“…This versatility of the G2P design storm makes it particularly useful in the context of practical urban hydrology applications at a regional scale. In fact, many studies estimating the impacts of global climate change present their results on a regional basis, referring results to expected spatial and temporal variations of given climatic or hydrological variables [52][53][54][55][56][57]. Such variables include precipitation, streamflow and temperature, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the AMS method provides flood event data that can be considered as independent and the frequency distributions generally conform to theoretical distributions [66]. For recent methodological developments in RFFA and its applications, see, for example, contributions about Canada [67] or Australia [68].…”
Section: Methodsmentioning
confidence: 99%
“…Identification of homogenous flood regions is a common RFA step prior to pooling flood information between similar catchments. Zhang and Stadnyk [19] evaluated multiple attributes, including geographic proximity, flood seasonality, physiographic variables, monthly precipitation and temperature patterns, to identify homogenous regions for RFA at 186 sites across Canada. They showed that the identification of homogenous regions relies on local hydrological complexities, representation of the primary flood mechanisms and geographic clustering of the sites.…”
Section: Summary Of This Special Issuementioning
confidence: 99%